2023
DOI: 10.1021/acs.nanolett.3c02399
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Aggregation of Clearable Bimetallic Nanoparticles with Interlocked Surface Motifs for Cancer Therapeutics Amplification

Abstract: Although renal-clearable luminescent metal nanoparticles (NPs) have been widely developed, their application to efficient cancer therapy is still limited due to low reactive oxygen species (ROS) production. Here, a novel system of clearable mercaptosuccinic acid (MSA) coated Au−Ag bimetallic NPs is designed to enhance ROS production. The results show that the strong COO−Ag coordination bonds between the carboxylic acid groups of MSA and Ag atoms on the Au−Ag bimetallic NPs could construct high-rigidity interlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…38 Therefore, the lack of a clear orientation in LC8 may be attributed to the excessive tendency for aggregation, leading to rapid molecular accumulation. On the other hand, this strong tendency for aggregation in LC8 may act as a detrimental factor in the photoinduced generation of ROS, 39,40 further leading to the self-degradation of the acceptor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…38 Therefore, the lack of a clear orientation in LC8 may be attributed to the excessive tendency for aggregation, leading to rapid molecular accumulation. On the other hand, this strong tendency for aggregation in LC8 may act as a detrimental factor in the photoinduced generation of ROS, 39,40 further leading to the self-degradation of the acceptor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[12] More recently, Tang et al found mercaptosuccinic acid (MSA) coated Au−Ag bimetallic NPs exhibited pH-responsive self-assembly capability by hydrogen bonding of carboxylic acid groups (O−H•••O) under the acidic environment inside lysosomes of cancer cells to enhance ROS production. [13] Furthermore, Cao and colleagues summarized the lysosomal targeting strategies including targeting lysosomal acidification, targeting lysosomal membrane permeability and integrity, and so on. [14] Excitingly, targeting lysosomal acidification has been used to design abundant lysosomal targeted and self-assembled nanosystems for antitumor and imaging.…”
Section: Introductionmentioning
confidence: 99%